Avaliação anti-inflamatória e antioxidante do extrato de tucumã (Astrocaryum aculeatum): estudos in vitro e in vivo - Cabral, Fernanda Licker (2018)
With the rise of new concepts such as functional foods, nutraceuticals and phytomedicines, allied to the use of traditional medicine, products of plant origin are in evidence. Brazil is a highlight in the development of new medicines from these products since it presents the greatest vegetal biodiversity in the world and occupies the third place in fruit production. Within this context, there is the Tucumã (Astrocaryum aculeatum), an Amazonian fruit widely used in the north of the country. Knowing the wide use and popular use as a treatment for several diseases, the objective of this work was to evaluate the antioxidant and anti- inflammatory effects of the Tucumã extract in different doses. For this, cultures of cells (RAW 264.7), activated with phytohemagglutinin (PHA) and treated with extract of A. aculeatum at doses of 1, 10, 30, 50, 100, 300 μg/ml were used. The results demonstrated an in vitro anti- inflammatory activity by decreasing the viability and proliferation of PHA-induced macrophages (P<0.05), modulating the cell cycle inducing G0/G1 (P<0.001) phase stay, decreased genes expression of the proinflammatory interleukin interleukin-1β (IL-1β) (P<0.001) and IL-6 (P<0.001) and increased genes expression of the IL-10 (P<0.01), anti- inflammatory, genes when compared to the PHA group. In addition, it was able to reduce the production of reactive oxygen and nitrogen species (ROS and NOs) and was genoprotective at the dose of 30 μg/ml (P<0.05). Later, in vivo tests were performed, where we used healthy Wistar rats in which the antioxidant and anti-inflammatory effects of the Tucumã extract were tested at doses of 250, 500, 1,000, 1,500mg/kg oral, by gavage, for 30 days. The animals were submitted to thoracotomy and blood, serum and tissues were collected. Blood count, serum albumin, cholesterol and triglycerides, as well as determination of the activity of the enzymes aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (FAL), butyrylcholinesterase (BuChE) and adenosine deaminase (ADA) in the serum. In the organs - liver, kidney, spleen and heart - the activity of the enzyme catalase (CAT), the presence of protein and non-protein thiols, thiobarbituric acid reactive substances (TBARS) and carbonylated proteins were evaluated, as well as ADA activity in the heart. The results suggest that the extract has anti-inflammatory potential since it was able to decrease the number of platelets (around 85%), leukocytes (49%), neutrophils (44%) and lymphocytes (48%) at all doses when compared to control. Most of the biochemical analyzes in the serum did not present statistical difference between the groups, evidencing only a reduction in the levels of triglycerides (66%) in the higher dosages. Similarly, the extract had no systemic effect, considering the activities of serum BuChE and ADA, which did not show any differences between the groups, except for the ADA activity in the cardiac tissue was decreased (P<0.01) at the dosages of 1,000 and 1,500 mg/kg when compared to control. Considering the organs, the extract proved its antioxidant and protective activity through the evident decrease of TBARS in the liver (P<0.001) at all doses tested when compared to the control. Thus, based on the results of the present study, we can infer that the extract of A. aculeatum has anti-inflammatory and antioxidant properties of natural occurrence with a promising possibility of being exploited for therapeutic purposes.